Consumption of artificial sweetened beverages associated with adiposity and increasing HbA1c in Hispanic youth. Issue 4 (12th June 2018) - Davis, J. N.; Asigbee, F. M.; Markowitz, A. K.; Landry, M. J.; Vandyousefi, S.; Khazaee, E.; Ghaddar, R.; Goran, M. I.
Summary: Research examining the impact of artificial sweetened beverages (ASBs) on obesity and metabolic diseases in adolescents is limited. The overall goal is to examine the longitudinal effects of ASBs on changes in adiposity and metabolic parameters in Hispanic adolescents. Longitudinal cohort with 98 Hispanics (12–18 years) who were overweight or had obesity with the following data at baseline and 1‐year later: anthropometrics, diet (24‐h recalls), body composition (DXA), glucose and insulin dynamics (oral glucose tolerance and frequently sampled intravenous glucose tolerance test) and fasting lipids. Repeated measures analyses of covariance assessed changes over time between control (no ASBs at either visit), ASB initiators (no ASBs at baseline/ASBs at 1‐year) and chronic ASB consumers (ASBs at both visits). ASB initiators ( n  = 14) and chronic ASB consumers ( n  = 9) compared to control ( n  = 75) had higher total body fat at baseline and 1‐year ( P  = 0.05 for group effect). Chronic ASB consumers had a 6% increase in haemoglobin A1c, 34% increase in energy intake (kcal d −1 ) and 39% increase in carbohydrate intake (g d −1 ) over time, while control and ASB initiators maintained ( P  < 0.05 for group‐by‐time interactions). These results do not support promoting ASBs as a strategy for adiposity loss or to improve metabolic health.